Christianisme, nomadisme et civilisation : une longue histoire mexicaine - Elisa Cárdenas Ayala (Nuevo mundo - Mundos Nuevos, 2023)
This article explores the weight of Christianity in the concept of civilization that accompanies the processes of secularization through the Mexican case. It also seeks to show this same concept takes up an experience prior to the arrival of Christianity to America, typical of the relations between the sedentary societies of the Valley of Anáhuac and the nomadic peoples, an experience that is concentrated in the term Chichimecas. The main hypothesis is that through the concept of civilization it is possible to perceive in the heart of the republic the articulation between the Christian colonial heritage and this older tradition, as well as its synthesis in discourses and political actions, particularly in the conception of both the territory and the national population.